Forensic pathology resources in the Philippines an annotated bibliography - Dela Cruz, Ayennerae Marienne P.; Santos, Mark Anthony A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study produced an annotated bibliography on forensic pathology resources. This includes both local and foreign resources - from the earliest possible to the latest possible resources-gathered from different libraries and databases. Aside from own research, the expert opinion of a Filipino forensic pathologist was sought in order gain insight of what terms are to be used during the search and what the contents of the resources should be. Each entry in the annotated bibliography is accompanied by a short paragraph which gives a description of its main purpose, contents, target audience, or special features, in order to serve as a ready reference or research tool to medical students, researchers, practitioners, professionals and by people interested or engaged in the field. Author and keyword indices are provided for ease of access for users.
This study produced an annotated bibliography on forensic pathology resources. This includes both local and foreign resources - from the earliest possible to the latest possible resources - gathered from different libraries and databases. Aside from own research, the expert opinion of a Filipino forensic pathologist was sought in order gain insight of what terms are to be used during the search and what the contents of the resources should be. Each entry in the annotated bibliography is accompanied by a short paragraph which gives a description of its main purpose, contents, target audience, or special features, in order to serve as a ready reference or research tool to medical students, researchers, practitioners, professionals and by people interested or engaged in the field. Author and keyword indices are provided for ease of access for users.
A significant number of readily available forensic pathology resources are present in the Philippines, print and electronic resources combined. Most of these resources are accessible through medical libraries and their respective subscriptions.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Forensic pathology -- Bibliography